2020
DOI: 10.1021/acsnano.0c01893
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Polar Adhesion with Traction, Spring, and Torque Forces Allows High-Speed Helical Migration of the Protozoan Parasite Toxoplasma

Abstract: Among the eukaryotic cells that navigate through fully developed metazoan tissues, protozoans from the Apicomplexa phylum have evolved motile developmental stages that move much faster than the fastest crawling cells owing to a peculiar substrate-dependent type of motility, known as gliding. Best-studied models are the Plasmodium sporozoite and the Toxoplasma tachyzoite polarized cells for which motility is vital to achieve their developmental programs in the metazoan hosts. The gliding machinery is shared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 64 publications
4
49
2
Order By: Relevance
“…The data also show clearly that the inhibitory effects of the palmitoylation inhibitor 2-bromopalmitate on parasite motility are not due to changes in palmitoylation of TgMLC1, as previously hypothesized, although changes in the palmitoylation of other glideosome components could be involved (64). While the data presented here do not, by themselves, disprove the linear motor model of motility, they add to a growing list of evidence (24)(25)(26)(27)(28)(29)33) suggesting that the mechanisms underlying apicomplexan parasite motility are more complicated than what is currently encapsulated by the linear motor model. How the different motility-associated proteins of the parasite interact and work together to generate the forces necessary to drive parasite movement and whether more than one underlying mechanism exists remain important open questions for future study.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The data also show clearly that the inhibitory effects of the palmitoylation inhibitor 2-bromopalmitate on parasite motility are not due to changes in palmitoylation of TgMLC1, as previously hypothesized, although changes in the palmitoylation of other glideosome components could be involved (64). While the data presented here do not, by themselves, disprove the linear motor model of motility, they add to a growing list of evidence (24)(25)(26)(27)(28)(29)33) suggesting that the mechanisms underlying apicomplexan parasite motility are more complicated than what is currently encapsulated by the linear motor model. How the different motility-associated proteins of the parasite interact and work together to generate the forces necessary to drive parasite movement and whether more than one underlying mechanism exists remain important open questions for future study.…”
Section: Discussionsupporting
confidence: 73%
“…While the importance of TgMyoA, TgMLC1 and the other glideosome components in motility is well established, recent data have called into question whether they are organized and function as described by the linear motor model and/or whether alternative motility mechanisms exist (24)(25)(26)(27)(28)(29). For example, the ability of apicomplexan parasites to rock back and forth on a substrate along their anterior to posterior axis (30)(31)(32)(33)(34)(35)(36) is hard to reconcile with the linear motor model, as is the ability of parasites engineered to lack key components of the glideosome to continue moving ( (24)(25)(26); see also (37)).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, gliding of sporozoites proceeds in a stick-slip manner that sees brief high instantaneous speed peaks followed by periods of lower speed [70]. Similar peaks of instantaneous speed have been observed in T. gondii tachyzoites [72], supporting a similar mechanism between the species. Recently, our understanding of T. gondii motility was also extended through an elegant combination of live-cell imaging and detailed analysis of traction forces.…”
Section: Marshalling Motility and Enveloping Entrysupporting
confidence: 62%
“…Recently, our understanding of T. gondii motility was also extended through an elegant combination of live-cell imaging and detailed analysis of traction forces. It was shown that tachyzoites can use the actinmyosin motor complex to induce increased curvature of the cortical microtubules [72]. This generates a spring-like force which powers forward motility by the parasite.…”
Section: Marshalling Motility and Enveloping Entrymentioning
confidence: 99%
See 1 more Smart Citation